Fertility and early embryonic development toxicity and toxicokinetic study of KFP‐H008 in Sprague–Dawley rats. Issue 8 (12th March 2022) - Lu, Bingbing; Yue, Peng; Shao, Qing; Mao, Lishun; Qiao, Hongqun
Abstract: The novel potassium competitive acid blocker, KFP‐H008, developed to overcome the shortcomings of proton pump inhibitors. In this study, KFP‐H008 was administered by oral gavage at doses of 0 (control), 15, 45, and 150 mg/kg to Sprague–Dawley rats (24 animals per sex per group). Body weight, food consumption, mortality, sexual cycle, mating behavior, pregnancy, sperm motility, and relative organ weights were evaluated. In a concomitant toxicokinetic (TK) study (10 animals per sex per group), plasma TK parameters and tissue distribution of KFP‐H008 were tested. There were obvious effects at the dosage of 150 mg/kg to male rats with decreases of prostate weight and lower weight gain; to female rats with lower weight gain, hair off, and lower corpus luteum count. There were no effects on litter parameters. Time to reach maximum plasma concentrations for KFP‐H008 was between 0.5 and 1.0 hr for the 15 and 45 mg/kg groups, while for the 150 mg/kg group it had a delay to 2 hr. Overall, the NOAEL of KFP‐H008 was considered to be 45 mg/kg in both genders and the TK study shows that exposure (area under the curve) of male rats was about 1, 091.0 ± 530.8 μg/Lhr and to female rats was 1, 030.5 ± 512.5 μg/Lhr. Administration of KFP‐H008although reaches the reproductive organs, it demonstrated no significant effects on reproductive organs, it did not affect mating, fertility, pregnancy, growth, or morphologic development.